Research and Application of Online Sampling Technology for Mercury and CO2 in Flue Gas Emission Continuous Monitoring Systems of Thermal Power Plants - Wang Zhiliang (PT. Publikasiku Academic Solution, 2025)
Monitoring emissions in thermal power plants requires high-accuracy and real-reliability systems, particularly for critical pollutants such as mercury (Hg) and carbon dioxide (CO2). Conventional manual sampling often faces limitations in response speed, data continuity, and representativeness, creating challenges for compliance with increasingly strict environmental regulations. This research aims to analyze the design, performance, and field application feasibility of an online sampling technology integrated within Continuous Emission Monitoring Systems (CEMS) specifically for Hg and CO2 in flue gas. The methodology includes a technical evaluation of sampling modules, assessment of sensor accuracy and stability, calibration and validation using reference methods, and on-site testing in a coal-fired thermal power plant. Data were analyzed through comparative measurements, response time analysis, and long-term operational reliability testing. Results indicate that online sampling technology significantly improves measurement continuity and reduces data fluctuation compared to manual sampling. The system demonstrates high accuracy, with CO2 measurement deviations within regulatory thresholds and mercury detection sensitivity enhanced through optimized temperature-controlled sampling lines. Additionally, technology reduces maintenance frequency by minimizing condensation and particulate interference, thereby increasing system uptime. Overall, the online sampling approach offers a more stable and efficient solutionfor emission monitoring and supports the implementation of stricter environmental compliance strategies in thermal power plants